ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KEPUASAN KINERJA KARYAWAN DIVISI TELESALES PT EKA MAS REPUBLIK CABANG BSD TANGERANG - Shavira, Aulia; Ratnawati, Whina (Journal of Research and Publication Innovation, 2024)
This research is entitled "Analysis of Work Motivation on Employee Performance Satisfaction in the Telesales Division of PT Eka Mas Republik BSD Tangerang Branch". This research aims to find out how much work motivation is experienced by employees of PT Eka Mas Republik Telesales Division. Using descriptive qualitative research methods, and the data collection techniques used are observation and interviews. This research was conducted with 3 informants who worked at this place. So the researchers found that the work motivation experienced by employees of PT Eka Mas Republik Telesales Division tended to be negative towards employee performance satisfaction. So with this lack of work motivation, companies must evaluate the occurrence of low work motivation in employees. Employee performance satisfaction at PT Eka Mas Republik Telesales Division tends to be negative, this can happen because employee performance is not recognized or there is a lack of appreciation for employee performance.